A novel natural GRAS-grade enteric coating for pharmaceutical and nutraceutical products - Khoder, Mouhamad; Schropp, Verena; Zeitler, Susanne; Pereira, Beatriz; Habashy, Rober; Royall, Paul G.; Wang, Julie Tzu Wen; Alhnan, Mohamed A. (International Journal of Pharmaceutics, 2020)
In this study, enteric coatings based exclusively on naturally occurring ingredients were reported. Alginate (Alg) and pectin (Pec) blends with or without naturally occurring glyceride, glycerol monostearate (GMS), were initially used to produce solvent-casted films. Incorporating GMS in the natural polymeric films significantly enhanced the acid-resistance properties in gastric medium. Theophylline tablets coated with Alg-Pec blends without GMS disintegrated shortly after incubation in gastric medium (pH 1.2), leading to a premature and complete release of theophylline. Interestingly, tablets coated with Alg-Pec blends that contain the natural glyceride (GMS) resisted the gastric environment for 2 h with minimal drug release (<5%) and disintegrated rapidly following introduction to the intestinal medium, allowing a fast and complete drug release. Furthermore, the coating system proved to be stable for six months under accelerated conditions. These findings are particularly appealing to nutraceutical industry as they provide the foundation to produce naturally-occurring GRAS based enteric coatings.
CRIS-Team Scopus Importer:2020-05-22
Keywords: Code oil; Delayed-release; Enteric-coatings; Gastro-resistant; Nutraceuticals; Probiotics

B Cells in Multiple Sclerosis and Virus-Induced Neuroinflammation - Chunder, Rittika; Schropp, Verena; Kürten, Stefanie (Frontiers in Neurology, 2020)
Neuroinflammation can be defined as an inflammatory response within the central nervous system (CNS) mediated by a complex crosstalk between CNS-resident and infiltrating immune cells from the periphery. Triggers for neuroinflammation not only include pathogens, trauma and toxic metabolites, but also autoimmune diseases such as neuromyelitis optica spectrum disorders and multiple sclerosis (MS) where the inflammatory response is recognized as a disease-escalating factor. B cells are not considered as the first responders of neuroinflammation, yet they have recently gained focus as a key component involved in the disease pathogenesis of several neuroinflammatory disorders like MS. Traditionally, the prime focus of the role of B cells in any disease, including neuroinflammatory diseases, was their ability to produce antibodies. While that may indeed be an important contribution of B cells in mediating disease pathogenesis, several lines of recent evidence indicate that B cells are multifunctional players during an inflammatory response, including their ability to present antigens and produce an array of cytokines. Moreover, interaction between B cells and other cellular components of the immune system or nervous system can either promote or dampen neuroinflammation depending on the disease. Given that the interest in B cells in neuroinflammation is relatively new, the precise roles that they play in the pathophysiology and progression of different neuroinflammatory disorders have not yet been well-elucidated. Furthermore, the possibility that they might change their function during the course of neuroinflammation adds another level of complexity and the puzzle remains incomplete. Indeed, advancing our knowledge on the role of B cells in neuroinflammation would also allow us to tackle these disorders better. Here, we review the available literature to explore the relationship between autoimmune and infectious neuroinflammation with a focus on the involvement of B cells in MS and viral infections of the CNS.
CRIS-Team Scopus Importer:2020-11-27
Keywords: B cells; central nervous system; EBV; multiple sclerosis; neuroinflammation; viral infection

Contribution of LTi and T(H)17 cells to B cell aggregate formation in the central nervous system in a mouse model of multiple sclerosis - Schropp, Verena; Rohde, Joern; Rovituso, Damiano M.; Jabari, Samir; Bharti, Richa; Kürten, Stefanie (Journal of Neuroinflammation, 2019)
BackgroundIn a subgroup of patients suffering from progressive multiple sclerosis (MS), which is an inflammation-mediated neurodegenerative disease of the central nervous system (CNS), B cell aggregates were discovered within the meninges. Occurrence of these structures was associated with a more severe disease course and cortical histopathology. We have developed the B cell-dependent MP4-induced experimental autoimmune encephalomyelitis (EAE) as a mouse model to mimic this trait of the human disease. The aim of this study was to determine a potential role of lymphoid tissue inducer (LTi) and T(H)17 cells in the process of B cell aggregate formation in the MP4 model.MethodsWe performed flow cytometry of cerebellar and splenic tissue of MP4-immunized mice in the acute and chronic stage of the disease to analyze the presence of CD3(-)CD5(-)CD4(+)RORt(+) LTi and CD3(+)CD5(+)CD4(+)RORt(+) T(H)17 cells. Myelin oligodendrocyte glycoprotein (MOG):35-55-induced EAE was used as B cell-independent control model. We further determined the gene expression profile of B cell aggregates using laser capture microdissection, followed by RNA sequencing.ResultsWhile we were able to detect LTi cells in the embryonic spleen and adult intestine, which served as positive controls, there was no evidence for the existence of such a population in acute or chronic EAE in neither of the two models. Yet, we detected CD3(-)CD5(-)CD4(-)RORt(+) innate lymphoid cells (ILCs) and T(H)17 cells in the CNS, the latterespecially in the chronic stage of MP4-induced EAE. Moreover, we observed a unique gene signature in CNS B cell aggregates compared to draining lymph nodes of MP4-immunized mice and to cerebellum as well as draining lymph nodes of mice with MOG:35-55-induced EAE.ConclusionThe absence of LTi cells in the cerebellum suggests that other cells might take over the function as an initiator of lymphoid tissue formation in the CNS. Overall, the development of ectopic lymphoid organs is a complex process based on an interplay between several molecules and signals. Here, we propose some potential candidates, which might be involved in the formation of B cell aggregates in the CNS of MP4-immunized mice.
CRIS-Team WoS Importer:2019-06-18

Differential effects of FTY720 on the B cell compartment in a mouse model of multiple sclerosis - Bail, Kathrin; Notz, Quirin; Rovituso, Damiano M.; Schampel, Andrea; Wunsch, Marie; Koeniger, Tobias; Schropp, Verena; Bharti, Richa; Scholz, Claus-Juergen; Foerstner, Konrad U.; Kleinschnitz, Christoph; Kuerten, Stefanie (Journal of Neuroinflammation, 2017)
BACKGROUND: MP4-induced experimental autoimmune encephalomyelitis (EAE) is a mouse model of multiple sclerosis (MS), which enables targeted research on B cells, currently much discussed protagonists in MS pathogenesis. Here, we used this model to study the impact of the S1P1 receptor modulator FTY720 (fingolimod) on the autoreactive B cell and antibody response both in the periphery and the central nervous system (CNS). METHODS: MP4-immunized mice were treated orally with FTY720 for 30 days at the peak of disease or 50 days after EAE onset. The subsequent disease course was monitored and the MP4-specific B cell/antibody response was measured by ELISPOT and ELISA. RNA sequencing was performed to determine any effects on B cell-relevant gene expression. S1P1 receptor expression by peripheral T and B cells, B cell subset distribution in the spleen and B cell infiltration into the CNS were studied by flow cytometry. The formation of B cell aggregates and of tertiary lymphoid organs (TLOs) was evaluated by histology and immunohistochemistry. Potential direct effects of FTY720 on B cell aggregation were studied in vitro. RESULTS: FTY720 significantly attenuated clinical EAE when treatment was initiated at the peak of EAE. While there was a significant reduction in the number of T cells in the blood after FTY720 treatment, B cells were only slightly diminished. Yet, there was evidence for the modulation of B cell receptor-mediated signaling upon FTY720 treatment. In addition, we detected a significant increase in the percentage of B220+ B cells in the spleen both in acute and chronic EAE. Whereas acute treatment completely abrogated B cell aggregate formation in the CNS, the numbers of infiltrating B cells and plasma cells were comparable between vehicle- and FTY720-treated mice. In addition, there was no effect on already developed aggregates in chronic EAE. In vitro B cell aggregation assays suggested the absence of a direct effect of FTY720 on B cell aggregation. However, FTY720 impacted the evolution of B cell aggregates into TLOs. CONCLUSIONS: The data suggest differential effects of FTY720 on the B cell compartment in MP4-induced EAE.
EVALuna2:35216

Effects of a Fully Humanized Type II Anti-CD20 Monoclonal Antibody on Peripheral and CNS B Cells in a Transgenic Mouse Model of Multiple Sclerosis - Tacke, Sabine; Chunder, Rittika; Schropp, Verena; Urich, Eduard; Kürten, Stefanie (International Journal of Molecular Sciences, 2022)
Successful therapy with anti-CD20 monoclonal antibodies (mAbs) has reinforced the key role of B cells in the immunopathology of multiple sclerosis (MS). This study aimed to determine the effects of a novel class of anti-CD20 mAbs on vascular and extravascular central nervous system (CNS)-infiltrating B cells in experimental autoimmune encephalomyelitis (EAE), an animal model of MS. Male hCD20xhIgR3 mice and wild-type C57BL/6 (B6) mice were immunized with human myelin oligodendrocyte glycoprotein (MOG)1–125 to induce EAE. While hCD20xhIgR3 mice were injected intravenously with an anti-human CD20 mAb (5 mg/kg) (rituximab (a type I anti-CD20 mAb) or obinutuzumab (a type II anti-CD20 mAb), B6 mice received the anti-mouse CD20 antibody 18B12. Neither mAb affected clinical disease or serum antibody levels. Obinutuzumab and rituxi-mab had an impact on splenic and CNS-infiltrated B cells with slightly differential depletion effi-cacy. Additionally, obinutuzumab had beneficial effects on spinal cord myelination. B cell depletion rates in the 18B12/B6 model were comparable with those observed in obinutuzumab-treated hCD20xhIgR3 mice. Our results demonstrate the usefulness of anti-CD20 mAbs for the modulation of B cell-driven peripheral immune response and CNS pathology, with type II antibodies potentially being superior to type I in the depletion of tissue-infiltrating B cells.
CRIS-Team Scopus Importer:2022-03-25
Keywords: B cells; CD20; Experimental autoimmune encephalomyelitis; Multiple sclerosis; Obinutuzumab; Rituximab

Obinutuzumab-induced b cell depletion reduces spinal cord pathology in a cd20 double transgenic mouse model of multiple sclerosis - Breakell, Thomas; Tacke, Sabine; Schropp, Verena; Zetterberg, Henrik; Blennow, Kaj; Urich, Eduard; Kürten, Stefanie (International Journal of Molecular Sciences, 2020)
B cell-depleting therapies have recently proven to be clinically highly successful in the treatment of multiple sclerosis (MS). This study aimed to determine the effects of the novel type II anti-human CD20 (huCD20) monoclonal antibody (mAb) obinutuzumab (OBZ) on spinal cord degeneration in a B cell-dependent mouse model of MS. Double transgenic huCD20xHIGR3 (CD20dbtg) mice, which express human CD20, were immunised with the myelin fusion protein MP4 to induce experimental autoimmune encephalomyelitis (EAE). Both light and electron microscopy were used to assess myelination and axonal pathology in mice treated with OBZ during chronic EAE. Furthermore, the effects of the already established murine anti-CD20 antibody 18B12 were assessed in C57BL/6 wild-type (wt) mice. In both models (18B12/wt and OBZ/CD20dbtg) anti-CD20 treatment significantly diminished the extent of spinal cord pathology. While 18B12 treatment mainly reduced the extent of axonal pathology, a significant decrease in demyelination and increase in remyelination were additionally observed in OBZ-treated mice. Hence, the data suggest that OBZ could have neuroprotective effects on the CNS, setting the drug apart from the currently available type I anti-CD20 antibodies.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Anti-CD20; B cells; EAE; MAb; Multiple sclerosis; Neurodegeneration; Obinutuzumab

Recombinant human gelsolin promotes the migration of human articular cartilage chondrocytes by regulating gene expression in vitro. - Feldt, Jessica; Welss, Jessica; Schropp, Verena; Gelse, Kolja; Tsokos, Michael; Paulsen, Friedrich (Osteoarthritis and Cartilage Open, 2020)
OBJECTIVE: It is known that recombinant human gelsolin (rhuGSN) supports wound closure and migration processes in avascular tissue. Since articular cartilage degradation plays an important role in osteoarthritis (OA), we are investigating how rhuGSN affects regeneration processes in human articular cartilage and represents a promising new therapeutic approach for the treatment of OA. METHODS: Primary human chondrocytes (phCs) from articular knee cartilage were cultured with different concentrations of rhuGSN to analyse its direct effect in vitro. In addition, phCs were stimulated with 10 ng/mL IL-1β or TNF-α to simulate osteoarthritis in vitro and treated with different concentrations of rhuGSN to investigate the beneficial effect in disease treatment. Cytokine secretion and gene expression as well as wound assays were performed. RESULTS: GSN significantly promotes wound closure in phCs after 60 h compared to untreated cells. After 24 h treatment with 30 μg/mL rhuGSN, TGF-β secretion increases significantly in the in vitro osteoarthritis model. Gene expression of MMP1 as well as SPARC is reduced in chondrocytes due to treatment with GSN in the OA model. At the same time, CXCR4 expression increases significantly after 24 h treatment with 3 μg/mL GSN. CONCLUSION: In the in vitro model of osteoarthritis, rhuGSN promotes wound closure of chondrocytes by a supported migration as well as expression of reconstructive and down regulated expression of deconstructive genes concentration dependently. Further experiments are needed to fully understand the beneficial effect of gelsolin on human chondrocytes and to verify this promising approach for a pharmacological treatment of osteoarthritis.
EVALuna2:515804

Same same but different: A Web-based deep learning application revealed classifying features for the histopathologic distinction of cortical malformations - Kubach, Joshua; Muhlebner-Fahrngruber, Angelika; Soylemezoglu, Figen; Miyata, Hajime; Niehusmann, Pitt; Honavar, Mrinalini; Rogerio, Fabio; Kim, Se-Hoon; Aronica, Eleonora; Garbelli, Rita; Vilz, Samuel; Popp, Alexander; et al. (Epilepsia, 2020)
Objective: The microscopic review of hematoxylin-eosin–stained images of focal cortical dysplasia type IIb and cortical tuber of tuberous sclerosis complex remains challenging. Both entities are distinct subtypes of human malformations of cortical development that share histopathological features consisting of neuronal dyslamination with dysmorphic neurons and balloon cells. We trained a convolutional neural network (CNN) to classify both entities and visualize the results. Additionally, we propose a new Web-based deep learning application as proof of concept of how deep learning could enter the pathologic routine. Methods: A digital processing pipeline was developed for a series of 56 cases of focal cortical dysplasia type IIb and cortical tuber of tuberous sclerosis complex to obtain 4000 regions of interest and 200 000 subsamples with different zoom and rotation angles to train a neural network. Guided gradient-weighted class activation maps (Guided Grad-CAMs) were generated to visualize morphological features used by the CNN to distinguish both entities. Results: Our best-performing network achieved 91% accuracy and 0.88 area under the receiver operating characteristic curve at the tile level for an unseen test set. Novel histopathologic patterns were found through the visualized Guided Grad-CAMs. These patterns were assembled into a classification score to augment decision-making in routine histopathology workup. This score was successfully validated by 11 expert neuropathologists and 12 nonexperts, boosting nonexperts to expert level performance. Significance: Our newly developed Web application combines the visualization of whole slide images with the possibility of deep learning–aided classification between focal cortical dysplasia IIb and tuberous sclerosis complex. This approach will help to introduce deep learning applications and visualization for the histopathologic diagnosis of rare and difficult-to-classify brain lesions.
CRIS-Team Scopus Importer:2020-03-06
Keywords: brain; convolutional neural network; cortical malformations; deep learning; digital pathology; epilepsy